The Effect of Talking Stick Learning Model Toward Students' History Learning Outcomes - Mariah Mariah; Sarkadi Sarkadi; Nuzengky Ibrahim (Universitas of Muhammadiyah Makassar, 2020)
Abstract. This eksperimental study aims to determine the effect and difference of talking stick learning. The research design used was posttest-Only Control Group design. The population in this study amounted to 78 students. Sampling technique uses cluster random sampling. This study uses a sample of two classes. Data collection methods using test and documentation. Data analysis using simple regression test and independent sample Ttest test using SPSS 19.0. the result of the analysis of simple regression test data are t count table, so Ho is rejected and Ha is accepted which means that there is influence of the use of cooperative learning model talking stick type on history studies learning outcomes of XI grade students of Pelita high school three. The result of analysis of independent sample t test tess data are t count t table, so Ho is rejected and Ha is accepted which means that there is a difference in the use of cooperative learning model talking stick type on history students learning outcomes of XI grade students Pelita high school three.Keywords: Talking Stick model, learning outcomes.Abstrak. Penelitian eksperimen ini bertujuan untuk mengetahui pengaruh dan perbedaan pembelajaran Talking Stick. Desain penelitian yang digunakan adalah desain post test kontrol grup. Populasi dalam penelitian ini berjumlah 78 siswa. Tekhnik pengambilan sampel menggunakan tekhnik random sampling. Penelitian ini menggunakan sampel dua kelas. Metode pengumpulan data menggunakan tes dan dokumentasi. Analisis data menggunakan uji regresi sederhana dan uji sampel independen Ttest menggunakan SPSS 19.0. Hasil analisis data uji regresi sederhana adalah t hitung tabel, sehingga Ho ditolak dan Ha diterima yang berarti ada pengaruh penggunaan model pembelajaran kooperatif tipe talking stick terhadap hasil belajar Sejarah siswa kelas XI IPS SMA Pelita Tiga. Hasil analisis data uji t sampel bebas adalah t hitung t tabel, sehingga Ho ditolak dan Ha diterima yang berarti ada perbedaan dalam penggunaan model pembelajaran kooperatif tipe talking stick pada hasil pembelajaran Sejarah siswa kelas XI IPS SMA Pelita Tiga.Kata Kunci: Model Talking Stick, Hasil belajar.